EVALUASI EFEKTIVITAS TEKNOLOGI AI DALAM MENINGKATKAN PERSONALISASI BELANJA DIGITAL - Anjar Asmara Putra; Lucia Rainy Betari; Jerry Heikal (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to evaluate the effectiveness of Artificial Intelligence (AI) technology in personalizing digital shopping experiences. Using a mixed-method approach that combines qualitative and quantitative methods, the research examines how AI algorithms such as machine learning, data-driven product recommendations, and intelligent chatbots contribute to enhancing customer satisfaction and loyalty on e-commerce platforms. Data were collected through surveys of active e-commerce users and in-depth interviews with platform developers. The findings reveal that AI significantly improves the relevance of product recommendations, the efficiency of customer service, and overall user engagement. The study concludes that AI plays a pivotal role in shaping digital marketing strategies and supporting customer retention efforts in the contemporary digital economy.